La conservación del patrimonio histórico-arquitectónico: ¿un sueño im-posible? - Arias-Quirós, Ana Cecilia (2012)
The authors explain their perspective on how the objectives of the Costa Rican Law N.° 7555 are carried out. This Law addresses the preservation of the national historic and architectural heritage. For several years, the authors have been members of the Commission created by Law 7555, thus their views are based on this experience. Putting into effect this Law has brought successes and failures. The procedures to declare officially that a given property is heritage both facilitate as well as hinder the purposes of preservation and conservation. Protection of the cultural heritage requires agreement on diverse levels of opinion and ways to carry out official norms, for example: 1) Education is necessary in order to change attitudes about the nature and meanings of historic architectural heritage. 2) Legislation should follow principles of conservation and assessment of the value of such heritage. 3) Scientific research should be the basis for taking decisions. 4) The State should define a public policy free of individual or sector interests and devoted to insuring the safeguard of the cultural heritage of the nation.